2022
DOI: 10.1177/26323524221101077
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic disclosure in cancer care: a systematic literature review

Abstract: Background: Collusion in cancer care is the diplomatic concealment of information between a triad of the health care professional (HCP), patient, and caregiver. Free and expressive communication is determined by multiple factors, which establishes a healthy balance between ‘patient-centric’ and ‘family-centric’ decision making. The lack of a universal approach to prognostic disclosure techniques emphasizes the need for a systematic review of contemporary practice. Methods: A systematic review of the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Allowing the patient to include their loved ones in remote conversations is crucial, especially if the patient is undergoing isolation and has limited opportunities to connect with others. Given the emotionally challenging nature of receiving a cancer diagnosis virtually while being in isolation, mental health professionals or palliative care specialists should also be involved, if necessary, to assist the patient in navigating through the process [ 1 ].…”
Section: Possible Ways Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Allowing the patient to include their loved ones in remote conversations is crucial, especially if the patient is undergoing isolation and has limited opportunities to connect with others. Given the emotionally challenging nature of receiving a cancer diagnosis virtually while being in isolation, mental health professionals or palliative care specialists should also be involved, if necessary, to assist the patient in navigating through the process [ 1 ].…”
Section: Possible Ways Forwardmentioning
confidence: 99%
“…Any disclosure of a life‐threatening event, such as a malignancy diagnosis, often causes significant stress to patients. While some patients may respond with acceptance and a determination to fight their illness, research has consistently shown that cancer patients often respond to the disclosure of their diagnosis with a range of negative emotions, such as anxiety, distress, and depression [ 1 , 2 ]. These reactions are often accompanied by feelings of fear, uncertainty, and a sense of loss of control over their lives.…”
Section: Introductionmentioning
confidence: 99%
“…A growing interest in the field of information given to patients with a diagnosis of cancer has spread in the last years ( Wan et al, 2020 ; Sutar and Chaudhary, 2022 ), leading to a consensus on the worldwide importance of cancer diagnosis awareness.…”
Section: Introductionmentioning
confidence: 99%
“…A growing interest in the field of information given to patients with a diagnosis of cancer has spread in the last years (Wan et al, 2020;Sutar and Chaudhary, 2022), leading to a consensus on the worldwide importance of cancer diagnosis awareness.…”
Section: Introductionmentioning
confidence: 99%